Analisis Penyebab Selisih Anggaran dan Realisasi Belanja Dalam Laporan Keuangan Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Gresik Tahun 2024 - Muhammad Amaris Gentasae; Nufidatul Mahmudah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Discrepancies between budget allocations and actual expenditures may reflect weaknesses in the processes of budget planning, implementation, and control, thereby affecting the effectiveness of public fund utilization. This study aims to analyze the factors causing the variance between budget allocations and expenditure realization in the 2024 financial statements of the Regional Civil Service and Human Resource Development Agency (BKPSDM) of Gresik Regency. The study employed a qualitative research method using a case study approach, supported by quantitative data obtained from official financial documents, including the Budget Implementation Document (DPA) and the Budget Realization Report. The findings indicate that the variance between the budget and expenditure realization was attributable to several factors, including changes in the staffing structure, changes in external policies issued by the central government, and changes in local government policies related to budget efficiency. The study implies that the BKPSDM of Gresik Regency should improve the accuracy of forecasting employee transfers, strengthen coordination with stakeholders at the central government level, and conduct more effective monitoring of the implementation of budget efficiency policies.